A sequential pre-cracking procedure to measure the mode-I fracture toughness of ultra pure bulk metallic glasses. (December 2017) - Bernard, C.; Keryvin, V.; Doquet, V.; Hin, S.; Yokoyama, Y.
Abstract: A dedicated fatigue pre-cracking method, performed successively under mode II and mode I, has been set up to initiate and propagate a crack close to the notch plane, which is particularly difficult to achieve using pure mode I loading on some ultra pure bulk metallic glasses, free from oxygen contamination. This method, was applied to a pure Zr55 Cu30 Al10 Ni5 (at.%) amorphous alloy, and allowed successful pre-cracking and reliable measurement of the apparent mode I fracture toughness. Graphical Abstract: